Peran Fintech dalam Meningkatkan Inklusi Keuangan di Tengah Resesi Ekonomi - immi Fiska Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial Financial inclusion supports sustainable economic growth, particularly in developing countries. Economic challenges, such as recessions, can exacerbate disparities in access to formal financial services. Low-income communities and micro-enterprises face increasing difficulties in obtaining financial support. Financial technology (fintech) has emerged as an innovative solution, expanding financial access through flexible and accessible digital services. This study aims to analyze the role of fintech in enhancing financial inclusion amid economic recessions while identifying the challenges and opportunities within the fintech industry. The research employs a qualitative descriptive method with a literature review approach. Data is sourced from academic journals, industry reports, and regulations related to fintech and financial inclusion. The findings indicate that fintech contributes to financial inclusion through digital payment services, peer-to-peer (P2P) lending, technology-based investments, and microinsurance. However, challenges such as regulatory constraints, data security, and financial literacy remain obstacles to optimizing fintech’s role. This study concludes that fintech plays a strategic role in promoting financial inclusion during economic recessions. Collaboration among regulators, fintech service providers, and the public is essential to ensure the sustainable, secure, and inclusive utilization of fintech.